Boronic acid functionalized graphene platforms for diabetic wound healing. (March 2020) - Beyranvand, Siamak; Pourghobadi, Zeinab; Sattari, Shabnam; Soleymani, Khadijeh; Donskyi, Ievgen; Gharabaghi, Mahdieh; Unger, Wolfgang E.S.; Farjanikish, Ghasem; Nayebzadeh, Hassan; Adeli, Mohsen
Abstract: While noncovalent interactions between graphene derivatives and biosystems are extensively studied, less knowledge about their covalent multivalent interactions at biointerfaces is available. Due to the affinity of boronic acids towards cis-diol bearing biosystems, graphene sheets with this functionality were synthesized and their covalent interactions with the bacteria and nematode were investigated. As expected, graphene platforms with boronic acid functionality were able to wrap bacteria and destroy it in a short time. Surprisingly, body of nematodes was ruptured and their viability decreased to 30% after 24 h incubation with the functionalized graphene sheets. Because of their antibacterial and antiparasitic activities as well as their ability for wound dressing, graphene platforms with the boronic acid functionality were further investigated for diabetic wound healing. In vivo experiments showed that graphene platforms are more efficient than the commercially available drug, phenytoin, and restore both infected and non-infected diabetic wounds in ten days. Taking advantage of their straightforward synthesis, strong interactions with different biosystems as well as their ability to heal diabetic wounds, the boronic acid functionalized graphene sheets are promising candidates for a broad range of future biomedical applications. Graphical abstract: Image 1